2016
DOI: 10.1371/journal.pone.0156473
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Relative Importance and Additive Effects of Maternal and Infant Risk Factors on Childhood Asthma

Abstract: There is an error in the first sentence of the conclusion section of the abstract. The correct sentence is: Early-life exposures, maternal UTI during pregnancy (maternal antibiotic use), mode of delivery, infant antibiotic use, and having no older siblings at home, are associated with an increased risk of childhood asthma in a cumulative manner, and for those continuous variables, a dose-dependent relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Wu et al identified dose-dependent relationships between risk of childhood asthma and maternal urinary tract infections (UTIs) during pregnancy or infant antibiotic use during the first year of life 15 . The increase in risk is presumably due to changes in the abundance and diversity of the host's commensal microbes, as demonstrated by Penders et al, who reported that antibiotic use in infancy was associated with decreased abundance of Bifidobacteria and Bacteroides 16 .…”
Section: Microbial Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al identified dose-dependent relationships between risk of childhood asthma and maternal urinary tract infections (UTIs) during pregnancy or infant antibiotic use during the first year of life 15 . The increase in risk is presumably due to changes in the abundance and diversity of the host's commensal microbes, as demonstrated by Penders et al, who reported that antibiotic use in infancy was associated with decreased abundance of Bifidobacteria and Bacteroides 16 .…”
Section: Microbial Exposurementioning
confidence: 99%
“…For instance, homes with dogs contain richer more diverse bacterial communities compared to homes without pets 33 . Differences in microbial exposure are seen with increasing family size 15 as well as with certain activities of the occupants, particularly farming. It has long been recognized that the prevalence of allergic disease amongst the children of farmers is lower than in non-farming families 28, 34-36 .…”
Section: Microbial Exposurementioning
confidence: 99%